Going to sleep and going to school: Linking bedtime to student absenteeism. (13th June 2021) - Gottfried, Michael A.; Kirksey, J. Jacob
Summary: Educators continuously regard health as being a major driver of school attendance. While physical health factors have been explored in regards to reducing student absenteeism, no attention has been given to the role of bedtime. The present study explored associations between having a regular bedtime, the hour of going to sleep, and school start time to student attendance. Our findings indicate that a regular bedtime reduces kindergartners' absences and decreases their likelihood of being chronically absent. However, the time of bed was not associated with absenteeism, nor was the start time of kindergarten each morning. Potential mechanisms involve school‐going routines and practices, and therefore we discuss how schools and communities can play an influential role in helping to address student absenteeism.